5-azacytidine promotes microspore embryogenesis initiation by decreasing global DNA methylation, but prevents subsequent embryo development in rapeseed and barley - Solís, María-Teresa; El-Tantawy, Ahmed-Abdalla; Cano, Vanesa; Risueño, María C.; Testillano, Pilar S. (Frontiers in Plant Science, 2015)
Microspores are reprogrammed by stress in vitro towards embryogenesis. This process is an important tool in breeding to obtain double-haploid plants. DNA methylation is a major epigenetic modification that changes in differentiation and proliferation. We have shown changes in global DNA methylation during microspore reprogramming. 5-Azacytidine (AzaC) cannot be methylated and leads to DNA hypomethylation. AzaC is a useful demethylating agent to study DNA dynamics, with a potential application in microspore embryogenesis. This work analyzes the effects of short and long AzaC treatments on microspore embryogenesis initiation and progression in two species, the dicot Brassica napus and the monocot Hordeum vulgare. This involved the quantitative analyses of proembryo and embryo production, the quantification of DNA methylation, 5mdC immunofluorescence and confocal microscopy, and the analysis of chromatin organization (condensation/ decondensation) by light and electron microscopy. Four days of AzaC treatments (2.5 µM) increased embryo induction, response associated with a decrease of DNA methylation, modified 5mdC and heterochromatin patterns compared to untreated embryos. By contrast, longer AzaC treatments diminished embryo production. Similar effects were found in both species, indicating that DNA demethylation promotes microspore reprogramming, totipotency acquisition and embryogenesis initiation, while embryo differentiation requires de novo DNA methylation and is prevented by AzaC. This suggests a role for DNA methylation in the repression of microspore reprogramming and possibly totipotency acquisition. Results provide new insights into the role of epigenetic modifications in microspore embryogenesis and suggest a potential benefit of inhibitors, such as AzaC, to improve the process efficiency in biotechnology and breeding programs.